Humans, other beings and the environment : harurwa (edible stinkbugs) and environmental conservation in Southeastern Zimbabwe - Mawere, Munyaradzi (Cambridge Scholars Publishing, 2015)
Humans, Other Beings and the Environment is an ethnographic study of the possibilities for the mutual, symbiotic co-existence of human beings, a unique species of forest insects and natural forests. The result of extensive fieldwork conducted over a period of thirteen months, the book highlights the continuum among humans, wild insects and environmental conservation outcomes in a specific environment of southeastern Norumedzo in rural Zimbabwe. In this respect, it describes interactions and relationships between humans, other beings and the natural forests to demonstrate how some aspects of th.
This volume is a revision of the author's PhD thesis.
Keywords: Human-animal relationships -- Zimbabwe -- Masvingo Province.; Stinkbugs -- Zimbabwe -- Masvingo Province.; Forest conservation -- Zimbabwe -- Masvingo Province.; Social & cultural anthropology, ethnography.; Physical anthropology.; True stories: discovery / historical / scientific.; SOCIAL SCIENCE -- Human Geography.; Forest conservation; Human-animal relationships; Stinkbugs; Zimbabwe -- Masvingo Province